The Judge's Considerations in Deciding Cases of Violence or Threats of Violence that Coerce a Minor Victim into Engaging in Sexual Intercourse with the Perpetrator or Another Person (Study of Decision No. 433/Pid.Sus/2022/PN. Kot) - Baharudin, Baharudin; Satria, Indah; Pangestu, Espana Yudhistira Lanang (The Future of Education Journal, 2026)
This study examines the basis for judges' considerations in issuing decisions on cases of violence or threats of violence that force minors to engage in sexual intercourse, with a focus on Decision Number 433/Pid.Sus/2022/Pn. Kot. The background of this study was driven by the rise in cases of sexual violence against children which often place children in vulnerable positions due to unequal power relations and dependence on adults. The case raised in this study highlights how psychological coercion is used by perpetrators to control underage victims. The problems in this study are: the factors causing perpetrators to commit crimes of violence or threats of violence that force underage victims to engage in sexual intercourse with them or with others based on the study of decision number 433/Pid.Sus/2022/PN. Kot. and the basis for judges' considerations in issuing decision number 433/Pid.Sus/2022/PN. Kot. The research method uses a normative juridical and empirical juridical approach. The normative legal approach is pursued through a literature review, examining relevant laws, doctrines, and legal literature. Meanwhile, the empirical approach involves interviews with parties involved or directly familiar with the case to obtain a factual picture of the application of the law in the field. The results of the study indicate that the causal factors of this crime originate from internal aspects in the form of deviant sexual desires from the perpetrator, as well as external aspects including the influence of the social environment, weak moral control, and the negative impact of technological developments. Regarding the judge's considerations, it was found that the decision was taken based on two main bases. Juridically, the judge assessed the fulfillment of the criminal elements in Article 81 paragraph (1) of the Child Protection Law by emphasizing the existence of psychological violence and pressure that made the victim helpless. Non-juridically, the judge considered the deep trauma experienced by the victim as well as the existence of peace efforts and compensation from the defendant's family as mitigating factors in imposing sanctions. The recommendation from this study is that the government and society should continue to focus on strengthening sexual education in schools, increasing the role of families and communities in building awareness of ethics and the impact of sexual violence, and disseminating correct information to the public.